Social stratification in higher education investment: An analysis of students' choices of college majors and pathways to future labor-market outcomes in Taiwan. (2022) - Yu, Patricia; Hsieh, Tzu-Ling
Highlights: Social stratification is in return to higher education in the post-expansion era. Social stratification appears in students' choices of college majors and pathways. Students' major-pathway choice patterns are associated with labor-market outcomes. The STEM persistence pattern promotes both students' occupational status and income. College integration raises the likelihood of following the STEM persistence pattern. Abstract: Higher education in Taiwan has expanded, and it has seen a corollary increase in stratification. Extending Tinto's institutional departure model, this study tests both the outcome of students' academic integration and the influence that campus social systems have on them with regard to shaping their choice of major and subsequent persistence in or departure from the academic department of choice. This study further tests the relationship of students' choice patterns of majors and pathways to future labor-market outcomes. By analyzing longitudinal survey data in Taiwan, which tracked the 1984-1985 born cohort from 2001-2015, this study finds that social class plays an important role in stratifying students' choices of majors and pathways, which in turn are important in shaping labor-market outcomes.